Conhecimento organizacional, inteligência competitiva e inteligência de negócio: dificuldades na implantação de um sistema de apoio à decisão - Mano, Ricardo Barcellos (2009)
Today, businesses look more and more technological tools that can assist their decisions on measures of time dwindling. The business intelligence is an evolution of decision support system and presents itself today as the most popular solution. This solution requires higher investments in technology resources (hardware and software), as well as to prepare people, and call for organizational change (strategic positioning and structure). Business intelligence, too, is intrinsically linked to competitive intelligence and knowledge management. The objective of this research is to raise the difficulties in deploying a decision support system based on business intelligence, given the obstacles and their position within the organizational knowledge. Exploratory research was chosen as methodological approach that includes literature review of classical references and most current study, completed by field survey using semi-structured interviews to prove or reject the difficulties pointed out. The conclusions point four dimensions for all the difficulties, the greatest difficulty is the size of data quality and that they directly interfere in the decisions, who directs the initiative imposes his view that may not be the business need, cost is not considered a problem, but the return of the solution is directly proportional to its investment, knowledge management does not exist in organizations which may compromise a more efficient development of business intelligence